Textile production and consumption in Roman provinces and in free Germania – a 21st century perspective - Kaczmarek, Zofia (Studia Europaea Gnesnensia, 2017)
The paper aims to present the state of research on Roman Period archaeological textiles and new, 21st century perspectives for further analyses. The textiles proves to be important from the viewpoint of provincial economy, trade and cultural exchange. That is why, a special emphasis is put on the textile types, which are called Roman imports.